2015
DOI: 10.1016/j.ijdevneu.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced differentiation of neural stem cells to neurons and promotion of neurite outgrowth by oxygen–glucose deprivation

Abstract: Stroke has become the leading cause of mortality worldwide. Hypoxic or ischemic insults are crucial factors mediating the neural damage in the brain tissue of stroke patients. Neural stem cells (NSCs) have been recognized as a promising tool for the treatment of ischemic stroke and other neurodegenerative diseases due to their inducible pluripotency. In this study, we aim to mimick the cerebral hypoxic-ischemic injury in vitro using oxygen-glucose deprivation (OGD) strategy, and evaluate the effects of OGD on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…In the second zone, marginally lower oxygen levels may promote expansion of neuroglial precursor populations, a phenomenon which has been observed in cell cultures with controlled hypoxia levels [11][12][13] . In the central region of still lower oxygen levels, stem cell pluripotency may be maintained, as has also been observed in cell cultures with controlled hypoxia levels [4][5][6]14 , although other evidence has also suggested that hypoxia can induce differentiation [9][10]18 . Finally, zone 4 represents a potential hypoxic region where cell function and viability are threatened.…”
Section: Multi-compartment Model and Basis For Neural Migration And Cmentioning
confidence: 64%
“…In the second zone, marginally lower oxygen levels may promote expansion of neuroglial precursor populations, a phenomenon which has been observed in cell cultures with controlled hypoxia levels [11][12][13] . In the central region of still lower oxygen levels, stem cell pluripotency may be maintained, as has also been observed in cell cultures with controlled hypoxia levels [4][5][6]14 , although other evidence has also suggested that hypoxia can induce differentiation [9][10]18 . Finally, zone 4 represents a potential hypoxic region where cell function and viability are threatened.…”
Section: Multi-compartment Model and Basis For Neural Migration And Cmentioning
confidence: 64%
“…The condition of incubator was controlled as followed: 1% O 2 , 5% CO 2 , 94% N 2 , 37°C. The cells were subjected to treatment of oxygen glucose deprivation at different periods (3, 5, 8, and 10 hr) (Wang, Yang, & Wang, 2015).…”
Section: Oxygen Glucose Deprivationmentioning
confidence: 99%
“…NSCs are pluripotent, undifferentiated and self‐renewing neuronal precursor cells. NSC's transplantation has been promulgated as a promisingly attractive strategy for spinal cord injury and neurodegenerative disorders . NSC can replace lost oligodendrocytes and neurons, and this replacement contributes to the restoration of motor function in animal models .…”
Section: Introductionmentioning
confidence: 99%